超音波手術機器 (ソノペット®) の鼻科手術への応用 - 舘野, 宏彦; 藤坂, 実千郎; 髙倉, 大匡; 將積, 日出夫 (JIBI INKOKA TEMBO, 2014)
We used the Sonopet® ultrasonic bone aspirator for endoscopic sinonasal surgery, including septoplasty (one case), dacryocystorhinostomy (five cases) and surgery for maxillary sinus mucocele (one case). The insertion and maneuverability of the tip of the Sonopet® in the sinonasal cavities were satisfactory. Bone fragmentation was smooth, gradual and limited on the contact area of the thin tip. Mechanical damage of mucosa and nearby structures was not observed. The Sonopet® is expected to use as the substitute of the standard surgical drills for sinonasal bone drilling applications.